PENDAMPINGAN REVITALISASI SUNGAI BERBASIS PARTISIPASI MASYARAKAT SEBAGAI WAHANA WISATA DESA DI KABUPATEN SIDOARJO - Mohammad Basuki Rahmat; Arie Indartono; Sintia Megawati; Aslikha Amalia; Ayu Lestari; Hana Malihatul; Novia Anggraini; Sekarsari Wibowo; Yuning Widiarti (Perkumpulan Legowo Cerdas Sejahtera, 2025)
Sidoarjo Regency is one of the major administrative regions in East Java that has actively pursued regional development initiatives to strengthen village-based tourism and local economic resilience. One of the strategic approaches adopted by the local government is river revitalization, which is designed not only to restore the ecological and hydrological functions of rivers, including their role as groundwater reserves, but also to enhance their potential as tourism and recreational assets. This approach reflects an integrated development strategy that combines environmental sustainability with community-based economic development. To support the implementation of these programs, the Shipbuilding Institute of Poltytechnic Surabaya (PPNS) has established a formal collaboration with the Sidoarjo Regency Government through the signing of a Memorandum of Understanding. This collaboration provides an institutional framework for PPNS to contribute to regional development through research activities, community engagement, and human resource capacity-building programs. As part of this collaboration, PPNS plays an active role in facilitating the transfer of knowledge and technical expertise to local stakeholders involved in village development initiatives. The river revitalization program has been implemented in several selected locations, including Sumorame Village and Kemantren Village, which have been identified as areas with potential for river-based tourism development. In these villages, PPNS provides academic and technical assistance to support the planning and implementation of river revitalization activities, with a particular focus on improving environmental quality, strengthening community participation, and enhancing the sustainability of tourism development. The findings of this study highlight the importance of institutional collaboration and academic involvement in ensuring the effective implementation of river revitalization as a strategy for sustainable village tourism development.